2019
DOI: 10.1002/aur.2239
|View full text |Cite
|
Sign up to set email alerts
|

Specific Functional Connectivity Patterns of Middle Temporal Gyrus Subregions in Children and Adults with Autism Spectrum Disorder

Abstract: As one of the key regions in the “social brain” network, the middle temporal gyrus (MTG) has been widely reported to be associated with autism spectrum disorder (ASD), but there have been contradictory results in terms of whether it shows hyperconnectivity or hypoconnectivity. Delineating roles of MTG at the subregional level may eliminate the observed inconsistencies and provide a new avenue to reveal the neurophysiologic mechanism of ASD. Thus, we first performed connectivity‐based parcellation using the Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 75 publications
(96 reference statements)
2
19
0
Order By: Relevance
“…Our findings suggest that disorganized processing of face stimuli is caused by the abnormal activation of the visual area of the brain. Multiple studies involving brain functional connectivity networks and behavioral experiments found that autism is abnormal in the inferior temporal gyrus, middle temporal gyrus, and fusiform gyrus, which supports our results in other ways [49]- [53]. In addition, there is evidence that visuospatial processing is related to the development of core autistic sociocommunicative impairments [54].…”
Section: A Abnormal Brain Regions With Significant Differencessupporting
confidence: 90%
“…Our findings suggest that disorganized processing of face stimuli is caused by the abnormal activation of the visual area of the brain. Multiple studies involving brain functional connectivity networks and behavioral experiments found that autism is abnormal in the inferior temporal gyrus, middle temporal gyrus, and fusiform gyrus, which supports our results in other ways [49]- [53]. In addition, there is evidence that visuospatial processing is related to the development of core autistic sociocommunicative impairments [54].…”
Section: A Abnormal Brain Regions With Significant Differencessupporting
confidence: 90%
“…The posterior MTG has been reported to be involved in social cognitive and language processing ( Xu et al, 2015 , 2019a ). The disrupted functional connectivity pattern of the posterior MTG is closely associated the autism spectrum disorder ( Xu et al, 2019b ). The sgACC is a key region for emotion, reward and decision making processing ( Johansen-Berg et al, 2008 ), and the structural abnormality has been identified in patients with chronic knee osteoarthritis pain ( Liao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methodological issues may also limit our understanding of neural mechanism underlying lexical tone perception observed in native speakers of tonal languages. For instance, the dominant experimental design of event‐related fMRI might outperform the approach of resting‐state fMRI (rs‐fMRI) in capturing the real‐time neural activity in response to language stimuli, but barely reveals the intrinsic functional coupling of the language network when participants are idle (Pliatsikas & Luk, ; Van Dijk et al, ; Wang et al, ; Wang et al, ; Xu et al, ; Xu et al, ). Nemerous rs‐fMRI studies reveal that the intrinsic state of bilinguals could be altered by their linguistic experience (Berken, Chai, Chen, Gracco, & Klein, ; Gullifer et al, ; Kousaie, Chai, Sander, & Klein, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%